2016
DOI: 10.14486/intjscs593
|View full text |Cite
|
Sign up to set email alerts
|

How Uncertainty Avoidance, Power Distance and Indulgence Affect Social Commerce Expenditure? An Investigation Based on Facebook

Abstract: The increasing popularity of social networking sites (SNS) in recent years paved the way for the emergence of social commerce. As a subset of e-commerce, s-commerce establishes the communication between companies and consumers through SNS and allows online shopping. However, online shopping through s-commerce varies substantially between different regions. The differences observed in consumer behaviour stem from the different cultural background every society has. This study analyses the effects of Hofstede's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…This study found that uncertainty avoidance has a negative significant effect on attitudes toward Facebook advertising. This result is confirmed by Yildirim and Barutçu (2016) who studied the effect of uncertainty avoidance on social media commerce expenditure through Facebook as a social media platform. Both scholars confirmed that uncertainty avoidance usually decreases consumers' willingness to indulge in the social media commerce and may even cause them to decrease their expenditure.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…This study found that uncertainty avoidance has a negative significant effect on attitudes toward Facebook advertising. This result is confirmed by Yildirim and Barutçu (2016) who studied the effect of uncertainty avoidance on social media commerce expenditure through Facebook as a social media platform. Both scholars confirmed that uncertainty avoidance usually decreases consumers' willingness to indulge in the social media commerce and may even cause them to decrease their expenditure.…”
Section: Resultssupporting
confidence: 59%
“…The scholars found that the degree of power distance is of significance and influences online buying, while there was no association found between power distance and consumers' attitudes toward online brands. However, a study by Yildirim and Barutçu (2016) found that power distance has a negative influence on social advertising, commerce expenditure through social platforms, individuals' decisions about using the internet and even their attitudes toward Facebook advertising.…”
Section: Resultsmentioning
confidence: 99%
“…A high INDU society allows relatively free gratification of the basic and natural human drives related to enjoying life and having fun [33]. In other words, high INDU societies indicate a tendency to optimism, and people in high INDU societies will be optimistic about new technologies [53,58]. Therefore, in countries with high INDU, the values for concern and WTP were low.…”
Section: Discussionmentioning
confidence: 99%
“…On individual level, men and women with high uncertainty avoidance levels, seem to feel anxious and stressed in unknown and unstructured situations (Ayoun & Moreo, 2008). Hence, in this case, it is reasonable to assume that buyers that has high UA would also lean towards avoiding risks (Hwa-Froelich & Vigil, 2004;Yildirim & Barutçu, 2016).In addition, Park and Burns (2005) showed that pathological gambling, which is a compulsive behavior, is in negative correlation to uncertainty avoidance. In addition, previous studies showed that compulsive consumption is positively correlated to risk-taking (Campbell 1976;Wallach & Kogan 1961).…”
Section: Relationship Between Masc and Ocbbmentioning
confidence: 98%